Investigation of the Lamellar Grains of Graft-type Polymer Electrolyte Membranes for Hydrogen Fuel Cell Application using Ultrasmall-angle X-ray Scattering - Hao, Lam Hoang; Hieu, Dinh Tran Trong; Long, Tran Hoang; Hoa, Dang Van; Danh, Tran Thanh; Man, Tran Van; Luan, Le Quang; Phuong, Huynh Truc; Hong, Pham Thi Thu; Tap, Tran Duy (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 4DO - 10.25073/2588-1140/vnunst.5216, 2021)
The extensive ultrasmall-angle X-ray scattering measurements are performed in order to investigate the changes of lamellar grains of poly(styrenesulfonic acid)-grafted poly(ethylene-co-tetrafluoroethylene) polymer electrolyte membranes (ETFE-PEMs) that occur during the alteration of grafting degree (GD) under dry and immersed conditions. The lamellar grains of three series of the samples (polystyrene-grafted ETFE films and dry and hydrated ETFE-PEMs) are formed during the grafting process and develop independently with the change of the lamellar stacks. Interestingly, three series of samples exhibit a very similar trend of lamellar grain at any GD and a significant amount of graft chains is observed directly in the region between the grains (GD £ 59%) and outside of the grain network structures (GD > 59%). This observation indicates: i) The formation of the lamellar grains; ii) The rapid changes in characteristic sizes of the lamellar grains compared with the lamellar stacks; and iii) The newly generated phases consisting of only the graft materials. These findings explain why the lamellar grains and the graft chains play an important role in the higher proton conductivity and compatible tensile strengths of the membranes, compared with Nafion, at the immersed and severe operating conditions.